Towards Chinese smart manufacturing ecosystem in the context of the one belt one road initiative. Issue 3 (9th November 2018) - Al-Sayed, Rafif; Yang, Jianhua
Abstract : Purpose: The purpose of this paper is to examine empirically China's determined thrust to attain a high level of technological innovation and the factors affecting moving towards a smart and sophisticated manufacturing ecosystem in conjunction with the Belt and Road Initiative (OBOR). Design/methodology/approach: This research provides empirical determination of the factors affecting moving towards smart manufacturing ecosystems in China. The method is based on combining two approaches: semi-structured interview and questionnaire-based with academics, experts and managers in various Chinese industrial sectors. The results are based on the multivariate analysis of the collected data. A case study of the current manufacturing ecosystem was also analyzed, in order to understand the present state as well as the potential for China's competitive edge in the developed OBOR countries. Findings: The results illustrate the importance of the infrastructure dimension comprising variables related to ecosystems, industrial clusters and Internet of Things IoT and other advanced technologies. A case study of the city of Shenzhen's transformation into a smart cluster for innovative manufacturing points out how China's OBOR initiative for regional collaboration will further transform the regional smart clusters into an ultra-large innovation based smart ecosystem. Originality/value: This research is the first to study China' policies towards playing a prominent role in the Fourth Industrial Revolution 4IR in the context of the OBOR initiative, through empirically defining the factors affecting moving towards a knowledge-intensive smart manufacturing ecosystem where the added value is mostly innovation based.